Comparison of infrarenal aortic balloon occlusion with internal iliac artery balloon occlusion for patients with placenta accreta - Youwen Mei; Hu Zhao; Hui Zhou; Huaibo Jing; Yonghong Lin (BMC, 2019)
Abstract Background The study was designed to compare the role of infrarenal aortic artery balloon occlusion (IAABC) with internal iliac artery balloon occlusion (IIABOC). Methods One hundred seventy-four cases with placenta accreta were retrospectively analyzed.74 cases who had IAABC were in group A, while the others who had IIABOC were in group B. Results Amount of estimated blood loss (EBL), the rate of major blood loss, the rate of blood transfusion and uterine packing, length of hospitalization were not different in both groups. The rate of uterine artery embolization (UAE), balloon occlusion time, operation time and fetus radiation dose in group A were less than those in group B. Conclusions IAABC resulted in better clinical outcomes than IIABOC.